2019
DOI: 10.1111/sms.13557
|View full text |Cite
|
Sign up to set email alerts
|

Device‐measured light‐intensity physical activity and mortality: A meta‐analysis

Abstract: Introduction:The association of light-intensity physical activity (LPA) with mortality is poorly understood. This meta-analysis of cohort studies aimed to examine the dose-response relationships between daily device-measured LPA and mortality in adults aged 18 or older and to explore whether the associations were independent of moderate-to-vigorous physical activity (MVPA). Methods: Searches for prospective cohort studies providing effect estimates of daily LPA (exposure) on all-cause mortality (outcome) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 52 publications
(179 reference statements)
1
38
0
1
Order By: Relevance
“…We defined the profile with the highest nonambulatory activity as "high sitters," noting that nonambulatory activities most likely included passive and active sitting activities, with some time potentially spent participating in standing activities (45). We defined the "balanced activity" profile as approaching recommended daily activity and sleep benchmarks for middle-aged to older adults (19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…We defined the profile with the highest nonambulatory activity as "high sitters," noting that nonambulatory activities most likely included passive and active sitting activities, with some time potentially spent participating in standing activities (45). We defined the "balanced activity" profile as approaching recommended daily activity and sleep benchmarks for middle-aged to older adults (19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…Isso pode ser um indicativo que tenham aumentando a intensidade da AF de leve que vinham realizando para AFMV. Apesar de evidências apresentarem que a AF leve traz benefícios à saúde 24 , a OMS preconiza que AFMV traz proteção às DCNTs 25 . Sendo esse, portanto, um resultado satisfatório para o GI.…”
Section: Discussionunclassified
“…7 Further, recent evidence also suggests the detrimental effects of sedentary behavior (SB) [10][11][12][13] and beneficial effects of light-intensity physical activity (LPA) on health. 5,6,14 For example, a meta-analysis of device-based measurement studies found that replacing SB time with LPA was favorably associated with all-cause mortality risk and cardiometabolic risk markers. 13 Therefore, there is a need to examine physical activity across the intensity spectrum, bouted or unbouted.…”
Section: Introductionmentioning
confidence: 99%